Anticoagulation with rivaroxaban for livedoid vasculopathy (RILIVA): a multicentre, single-arm, open-label, phase 2a, proof-of-concept trial - Weishaupt, Carsten; Schneider, Stefan W. (The lancet. Haematology, 2016)
Background: Livedoid vasculopathy is a thrombotic skin disease characterised by recurrent occlusion of the cutaneous microcirculation in lower extremities, which results in skin infarctions with painful ulcerations and irreversible scar formation. Rivaroxaban is a direct factor Xa inhibitor that prevents thrombus formation. We investigated whether rivaroxaban is effective for the treatment of livedoid vasculopathy. Methods: We did this single-arm, open-label, multicenter, phase 2a, proof-of concept trial at three university hospitals in Germany. Patients with livedoid vasculopathy and a minimum pain score of 40 on the visual analogue scale were eligible to participate. Patients received oral rivaroxaban tablets for 12 weeks at an initial dose of 10 mg twice per day, which was reduced to once per day if a reduction of pain by 50% on the visual analogue scale was achieved. Subcutaneous enoxaparin at 1 mg per kg bodyweight once or twice per day was allowed as a backup treatment in case of insufficient efficacy and increased pain. The primary endpoint was change in pain on the visual analogue scale from baseline to 12 weeks. Efficacy was assessed in the intention-to-treat population and safety was assessed in all patients who received at least one dose of study drug. This trial is registered with the EU Clinical Trials Register, EudraCT number 2012-000108-13-DE, and is closed to new participants. Findings: Between Dec 28, 2012, and April 24, 2014, 36 patients were screened, 28 patients were recruited for the study, and 25 patients received treatment. During treatment, five patients dropped out of the study because of withdrawal of consent (one patient), lack of compliance (one patient), violation of inclusion criteria (two patients), and a serious adverse event (one patient). Median pain on the visual analogue scale decreased from 65·0 (IQR 52·0-78·0) at baseline to 6·0 (1·0-14·0) after 12 weeks of treatment (p<0·0001). Six of the 20 patients required additional treatment with enoxaparin. Eight treatment-related adverse events were recorded in six (24%) of the 25 patients: five cases of menorrhagia including one classified as both menorrhagia and dysmenorrhoea, one case of dyspnoea, and one case of gingival bleeding. The only serious adverse reaction to rivaroxaban during the study was one case of menorrhagia in a patient with concomitant endometriosis, which resulted in study discontinuation. Interpretation: Rivaroxaban seems to effectively reduce pain in livedoid vasculopathy. Therefore we suggest that rivaroxaban with enoxaparin as a backup treatment is a suitable treatment option for patients with livedoid vasculopathy.
Gesehen am 11.02.2019